Development of Polyvinylidene fluoride (PVDF)-ZIF-8 Membrane for Wastewater Treatment - Ibrahim, N.A. (Institute of Physics Publishing, 2018)
Nowadays, the water shortage problem following the urbanization and increasing pollution of natural water source have increased the awareness to treat wastewater. Membrane filtration is often used in wastewater treatment plants to filter out more residual activated sludge from aeration process in the secondary stage. However, fouling is the main concern due to the fact it can happen to any membrane application. Antifouling properties in membrane can be improved by blending membranes with fillers or additives to make them more hydrophilic. This study aims to improve the antifouling properties in polyvinylidene fluoride (PVDF) membranes while optimizing the loading of Zeolitic imidazolate framework-8 (ZIF-8) fillers; at different loading (2.0 wt. , 4.0 wt. , 6.0 wt. , 8.0 wt. and 10.0 wt. ). Manual hand-casting of flat sheet membrane was done and the fabricated membranes were tested for their filterability against pure water and domestic wastewater. Both permeability tests showed that PVDF with 8 ZIF-8 membrane was the most permeable with a pure water and wastewater permeability of 150 L/m2.h.bar and 94 L/m2.h.bar, respectively. The pure water permeability of PVDF with 8 ZIF-8 membrane increases for about 130 compared to the pure PVDF membrane. The turbidity test of the initial feed and final permeate of wastewater, PVDF with 8 ZIF-8 membrane also gave out the highest reduction rate at 87, which is 36 higher than that of pure PVDF membrane. It can be deduced that 8 of ZIF-8 is the ideal loading to PVDF in improving its antifouling properties to be used in domestic wastewater treatment. Â© 2018 Published under licence by IOP Publishing Ltd.